STUDI KELAYAKAN SIMPANG TAK SEBIDANG JALAN NASIONAL KUTOWIANGUN KEBUMEN, JAWA TENGAH - Darmadi (FTSP Universitas Jayabaya, 2021)
To evaluate the benefits of the project being built, an economic analysis is carried out using Net Present Value (NPV), Benefit Cost Ratio (BCR), and Economic Internal Rate of Return (EIRR). The analysis resulted in NPV of Rp 178,249,491,541, BCR of 1.86, and EIRR of 18.85%. From the values of BCR, NPV, and IRR it can be seen that this project is economically feasible. Furthermore, a sensitivity test of the NPV, BCR and IRR values were conducted in this study. From the sensitivity test of the NPV, BCR and IRR values, the R2 > 0.6 is obtained, so it can be concluded that the feasibility model is quite accurate to be applied to this project. The flyover alternative crossing the railway will be technically feasible, economically viable, environmentally and socially sustainable, and will contribute to the overall economic growth of the country, which should support poverty reduction and improved living standards.